PENERAPAN MODEL PEMBELAJARAN INDUCTIVE THINKING BERBASIS KETERAMPILAN PROSES SAINS UNTUK MENINGKATKAN KUALITAS PEMBELAJARAN BIOLOGI SISWA KELAS X.7 SMA NEGERI 2 KARANGANYAR TAHUN PELAJARAN 2011/2012 - Listyaningrum, Rahmawati Ika; Sajidan, Sajidan; Suciati, Suciati (Pendidikan Biologi, 2012)
ABSTRACT ? The aim of this research is improve quality of biology learning for teacher?s performance, utility of facilities in the classroom, classroom climate, science attitude of student, and student motivation of achievement in student class X.7 in 2th senior high school of Karanganyar in academic year 2011/2012. This research belongs to classroom action research consist of three cycle and each have four phases, namely  planning, acting, observing, and reflecting. The collecting data of research uses questionnaire, observation, and interview. Validation data uses triangulation of methods and triangulation of observers. The research uses analyzed descriptively.  The result in cycles I describes that generally the research target is not achieve yet that showed teacher?s performance indicators are 86,67%, classroom climate indicators are 72,79%, science attitude of students in class are 69,12%, and motivation of achievement in students are 68,63%. The result in cycles II describes that the research target is not achieve yet optimally that showed teacher?s performance indicators are 96,67%, classroom climate indicators are 78,67%, science attitude of students in class are 75,98%,  and motivation of achievement in students are 74,18%. The result in cycles III describes that the research target is completely achieve and showed that teacher?s performance indicators are 100%,  , classroom climate  indicators are 91,18%, science attitude of students in class are 84,31%, and motivation of achievement in students are 84,31% and utility of learning facilities in the classroom have been optimally. Cycles stopped in cycles III because the research target is achieved. The conclusion of this research describes that the implementation of inductive thinking learning model based science process skills can improve  quality of biology learning for  teacher?s performance, utility of facilities in the classroom,  classroom climate, science attitude of student, and motivation of achievement in student of class X.7 in 2th senior high school of Karanganyar year 2011/2012. Keywords : Inductive thinking, Science process skills, Quality of biology learning